2015
DOI: 10.3892/or.2015.3757
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of c-Myc by let-7b mimic reverses mutidrug resistance in gastric cancer cells

Abstract: Abstract. Chemotherapy is one of the few effective choices for patients with advanced or recurrent gastric cancer (GC). However, the development of mutidrug resistance (MDR) to cancer chemotherapy is a major obstacle to the effective treatment of advanced GC. Additionally, the mechanism of MDR remains to be determined. In the present study, we tested IC 50 of cisplating (DDP), vincristine (VCR) and 5-fluorouracil (5-FU) in SGC7901, SGC7901/DDP and SGC7901/VCR gastric cancer cells using an MTT assay. The expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 48 publications
(51 reference statements)
1
35
0
Order By: Relevance
“…In addition, various studies found miRNAs may be upstream regulators of c-Myc by targeting its mRNA, then inhibiting its translation (34,35). In addition, miRNA has been proved to be able to regulate chemoresistance of cancer cells by inhibiting c-Myc (36,37). The present study confirmed that c-Myc was directly targeted by miR-451 in bladder cancer.…”
Section: Discussionsupporting
confidence: 80%
“…In addition, various studies found miRNAs may be upstream regulators of c-Myc by targeting its mRNA, then inhibiting its translation (34,35). In addition, miRNA has been proved to be able to regulate chemoresistance of cancer cells by inhibiting c-Myc (36,37). The present study confirmed that c-Myc was directly targeted by miR-451 in bladder cancer.…”
Section: Discussionsupporting
confidence: 80%
“…Insulin like growth factor 2 mRNA binding proteins (IGF2BP1, IGF2BP2, IGF2BP3), high mobility group AT-hook 1 (HMGA1), ARID3B, and MYC protooncogene (c-MYC) are all let-7 miRNA targets with known roles in cell proliferation [18,[35][36][37][38][39][40][41]. IGF2BPs are highly conserved RNA binding oncofetal proteins with three paralogs, IGF2BP1, IGF2BP2, and IGF2BP3 [42].…”
Section: Introductionmentioning
confidence: 99%
“…Combinatorial treatment for NSCLC with let-7b and miR-34a resulted in the strongest synergistic enhancement of the efficacy of erlotinib. In addition, transfection with let-7b is known to reverse drug sensitivity in chemotherapy-resistant SGC7901/DDP and SGC7901/ VCR gastric cancer cells by targeting the downregulation of c-Myc [57]. These results indicate that let-7 miRNAs can effectively reverse drug resistance and can be used as adjuvant therapeutics for the treatment of human cancers to modulate chemotherapy and radiation resistance [58,59].…”
Section: Restoration Of Let-7 Expression Shows Therapeutic Effects Inmentioning
confidence: 90%